Case Report: Hypergranular Platelets in Vaccine-Induced Thrombotic Thrombocytopenia After ChAdOx1 nCov-19 Vaccination - Comer, Shane P.; Le Chevillier, Ana; Szklanna, Paulina B.; Kelliher, Sarah; Saeed, Khalid; Cullen, Steven; Edebiri, Osasere; O'Neill, Tiina; Stephens, Niamh; Weiss, Luisa; Murphy, Claire A.; Rajakumar, Saraswathi; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Vaccine-induced thrombotic thrombocytopenia (VITT) post SARS-CoV-2 vaccination is characterized by thrombocytopenia and severe thrombosis. Platelet function during patient recovery in the medium-/long-term has not been investigated fully. Here, we undertook a 3-month study, assessing the recovery of a VITT patient and assessing platelet morphology, granule content and dense-granule release at two distinct time points during recovery. Case Presentation A 61 year-old female was admitted to hospital 15 days post ChAdOx1 nCov-19 vaccination. Hematological parameters and peripheral blood smears were monitored over 3 months. Platelet morphology and granule populations were assessed using transmission electron microscopy (TEM) at two distinct time points during recovery, as was agonist-induced platelet dense-granule release. Upon admission, the patient had reduced platelet counts, increased D-dimer and high anti-PF4 antibodies with multiple sites of cerebral venous sinus thrombosis (CVST). Peripheral blood smears revealed the presence of large, hypergranular platelets. Following treatment, hematological parameters returned to normal ranges over the study period. Anti-PF4 antibodies remained persistently high up to 90 days post-admission. Two days after admission, VITT platelets contained more granules per-platelet when compared to day 72 and healthy platelets. Additionally, maximal ATP release (marker of dense-granule release) was increased on day 2 compared to day 72 and healthy control platelets. Conclusion This study highlights a previously unreported observation of platelet hypergranularity in VITT which may contribute to the thrombotic risk associated with VITT. Optimal approaches to monitoring recovery from VITT over time remains to be determined but our findings may help inform therapeutic decisions relating to anticoagulation treatment in this novel pathology.